Static Stability Determination Of An Exhaust Stack Structure Using Finite Element Analysis / Kamarul Nizam Hassan ... [et al.] - Hassan, Kamarul Nizam; Hussain, Ahmad Kamil; Mahmud, Jamaluddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The stability analysis of exhaust stack is generally governed by two physical factors, i.e. the intricacy of the stack shape and the height-to-diameter ratio and the nature of the the loadings it supports. In this study, an A516 Grade 70 steel cylindrical tubing exhaust stack subjected to its self-weight and wind speed of 7 m/s was analysed for static stability by applying the equilibrium of rigid body and strength of materials principles. Further analysis was conducted using the finite element simulation. Both results were then compared. The stack's stability state was assessed on the capability of the stack to withstand the maximum deflection and the maximum shear stresses. The complexity of the stack orientation caused a slight inaccuracy in the results. The computation for the volumes was slightly overestimate hence affecting the accuracy in the calculation values of the stack's own load and the determination of CG. As expected the maximum deflection occurred at the top free end of the exhaust stack. In addition the maximum shear stress was found to not exceed the maximum allowable shear stress for the studied model. Discussion on the vortex shedding was also presented. Vortex shedding developed when the wind flow passed across the cylindrical. From the FEM results, the vortex shedding had little effect to the stresses and displacement of the exhaust stack design.